Handle with Care: Implementation of the List Experiment and Crosswise Model in a Large-scale Survey on Academic Misconduct. Issue 1 (February 2022) - Jerke, Julia; Johann, David; Rauhut, Heiko; Thomas, Kathrin; Velicu, Antonia
This research analyzes the effectiveness of the list experiment and crosswise model in measuring self-plagiarism and data manipulation. Both methods were implemented in a large-scale survey of academics on social norms and academic misconduct. As the results lend little confidence about the effectiveness of the methods, researchers are best advised to avoid them or, at best, to handle them with care.